Optimization of MWCNT concentration in nylon-based nanocomposites for enhanced triboelectric nanogenerator performance - Orkhan Gulahmadov; Lala Gahramanli; Mustafa Muradov; Jadranka Blazhevska Gilev; Stefano Bellucci; Cristian Vacacela Gomez (Journal of Materials Science: Materials in Engineering)
Abstract This study explores the optimization of multi-walled carbon nanotube (MWCNT) concentration in nylon-based nanocomposites to enhance the performance of triboelectric nanogenerators (TENGs). Nylon/MWCNT nanocomposite films were fabricated using the spin-coating method, and their electrical output was systematically evaluated as a function of MWCNT concentration. Results show that the open-circuit voltage (Voc) and short-circuit current (Isc) increase with MWCNT loading up to 0.05 wt%, reaching a peak of 29.7 V and 3.0 μA, respectively, compared to 17.5 V and 1.8 μA for pristine nylon-based TENGs. However, a decline in output was observed at 0.1 wt% due to MWCNT agglomeration, which disrupts charge transfer and introduces charge leakage. The enhancement at optimal concentration is attributed to improved charge trapping and increased dielectric constant, while excessive CNT loading reduces the effective contact area and limits triboelectric charge generation. These findings underscore the crucial role of nanomaterial dispersion in optimizing TENG performance and offer valuable insights for the development of high-efficiency triboelectric energy harvesting systems.